Chewing lice of Bearded Reedling (Panurus biarmicus) and diversity of louse-host associations of birds in reed beds in Slovakia - Sychra Oldřich; Sušilová Lucie; Najer Tomáš; Literák Ivan; Papoušek Ivo; Martinů Jana; Trnka Alfréd; Capek Miroslav (Parasite, 2024)
A total of 1,621 wild birds representing 34 species were examined for chewing lice in reed beds in southwestern Slovakia during the pre-breeding migration 2008–2009 and 2016–2019. A total of 377 (23.3%) birds representing 15 species were parasitized by 26 species of chewing lice of 12 genera. Dominant genera were Penenirmus (with dominance 32.6%) and Menacanthus (29.4%), followed by Brueelia (12.6%), Acronirmus (10.8%), Philopterus (7.7%), and Myrsidea (4.2%). We evaluated 33 host-louse associations including both 1) host-generalist, parasitizing more than one host species and host-specific lice, occurring only on a single host species, and 2) lice species with large range geographic distribution, reported across the range of the distribution of their hosts and lice species with only occasional records from a limited area within the range of their hosts. The Bearded Reedling, Panurus biarmicus (Linnaeus, 1758), was parasitized by two species of chewing lice, Menacanthus brelihi Balát, 1981 and Penenirmus visendus (Złotorzycka, 1964), with conspicuously different prevalences (5.6% vs. 58.2%, respectively; n = 251). New material enabled us to redescribe both species of lice: the first one is resurrected from previous synonymy as a valid species. A fragment of the mitochondrial cytochrome oxidase I gene was sequenced from these two species in order to assess their relative phylogenetic position within their genera. Our study demonstrates the importance of an adequate identification of parasites, especially on rarely examined and endangered hosts.